Betaine: A Promising Natural Product for Neurological and Psychiatric Diseases - Zhang, Ying; Ke, Zhaojuan; Luo, Jie; Chen, Qibin; Jiang, Xin; Xiong, Jialin; Deng, Linya (Current Neuropharmacology, 2025)
Neurological and psychiatric diseases pose a considerable global burden. Exploring additional potential prevention strategies and therapies is ongoing. As a prevalent natural product and nutraceutical from food, betaine’s pharmaceutical applications suggest benefits for both health and disease in multiple organs. Recently, its efficacy on neurological and psychiatric health has been proposed and has drawn considerable attention. This review aims to provide an updated, critical, and comprehensive profile of the promising medicinal roles of betaine in these diseases. In addition to its well-known osmotic protection, due to methyl donation, it regulates metabolism, alleviates oxidative stress, and reduces inflammation. To manifest neurological and psychiatric health benefits, betaine acts by affecting gamma-aminobutyric acid associated with its transporters, related neurotransmitters, downstream and neurological pathways, and other specific mechanisms in the nervous system. Betaine demonstrates therapeutic potential against various neurological and psychiatric diseases, such as epilepsy, neurocognitive disorders (including Alzheimer's disease), Parkinson's disease, stroke, multiple sclerosis, traumatic brain injury, depression, anxiety, schizophrenia, autism spectrum disorder, sleep disorders, fetal alcohol syndrome, syringomyelia, neonatal brain injury, neuropathic pain, and motor dysfunction. Despite the promising role of betaine in the treatment, diagnosis, and prevention of neuropsychiatric disorders, much of the present evidence appears to be fragmentary. Further studies elucidating the underlying mechanisms and direct clinical applications are required to obtain a deeper understanding of betaine and its underutilized potential. Overall, this review highlights the potential of betaine as a promising agent with benefits for neurological and psychiatric diseases, aiming to offer clues to advance this field.
Keywords: gamma-aminobutyric acid